(untitled) (The Harvest, 2025)
This study examines the socioeconomic dynamics of returning Nepali migrant workers, focusing on their limited ability to achieve upward social mobility despite increased economic capital. Drawing on Bourdieu’s (1984) framework of capital and distinction, the research highlights how the acquisition of financial resources enables returning workers to enhance their lifestyle and consumption patterns but fails to bridge the gap in cultural and social capital required for social class elevation. The symbolic boundaries formed between returnees and traditional working-class individuals create a new “neo-lower class” that further entrenches social stratification and perpetuates inequality. Additionally, the study explores how migrant workers’ economic practices, such as gentrification and their influence on youth to pursue foreign employment, eternalize cycles of social class reproduction and migration. Despite breaking cycles of poverty within their families and contributing significantly to Nepal’s economy, these returnees remain excluded from elite social circles due to their lack of embodied cultural and social capital. The findings suggest that upward social mobility requires a holistic acquisition of economic, cultural, and social capital, underscoring the structural barriers faced by migrant workers in their pursuit of legitimacy and recognition in Nepalese society.